Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1364/oe.424414
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced on-chip terahertz vibrational absorption spectroscopy using evanescent fields in silicon waveguide structures

Abstract: In this study, we demonstrate on-chip terahertz absorption spectroscopy using dielectric waveguide structures. The structures’ evanescent fields interact with the sample material surrounding the waveguide, enabling the absorption signature of the material to be captured. The ability of fabricated terahertz dielectric waveguide structures, based on the newly developed silicon-BCB-quartz platform, to capture the fingerprint of α-lactose powder (as an example material) at 532 GHz is examined. Enhancement of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Among them, the THz waveguide transmission technology with low loss, long distance, and low dispersion is very essential due to the signal distortion in free space, the attenuation caused by atmospheric scattering, and the water vapor absorption. Various THz waveguides have been proposed and investigated, such as hollow metallic structures [20], metal wires [21], dielectric waveguides [22], parallel plate structures [23], photonic crystal fibers [24], [25], rectangular structures [26], plasmonic [27], and tapered waveguide [28]. However, most of researchers focused on the low loss and low dispersion THz waveguides and paid little attention to the transverse standing waves (i.e., the guided wave modes).…”
mentioning
confidence: 99%
“…Among them, the THz waveguide transmission technology with low loss, long distance, and low dispersion is very essential due to the signal distortion in free space, the attenuation caused by atmospheric scattering, and the water vapor absorption. Various THz waveguides have been proposed and investigated, such as hollow metallic structures [20], metal wires [21], dielectric waveguides [22], parallel plate structures [23], photonic crystal fibers [24], [25], rectangular structures [26], plasmonic [27], and tapered waveguide [28]. However, most of researchers focused on the low loss and low dispersion THz waveguides and paid little attention to the transverse standing waves (i.e., the guided wave modes).…”
mentioning
confidence: 99%
“…Traditional absorption spectroscopy measurement facilities usually use more sample materials since the diffraction of terahertz waves. 9 The current measurement of the terahertz absorption spectrum of solid samples processed by the tablet-pressing technique usually requires several hundred milligrams to several grams of the material to be measured. The interaction distance between the terahertz waves and the sample may limit the necessary amount of the samples.…”
Section: Introductionmentioning
confidence: 99%
“…For improving the sensitivity of terahertz absorption spectroscopy detection, additional enhanced structures, including photonic crystal fibers, resonant cavity, metal gratings, metal split ring resonators, and dielectric metasurface structures, are required to boost the interaction between the electromagnetic wave and sample material. Among these structures, the waveguides [9][10][11] and metasurfaces [12][13][14][15] have been treated in the sensing applications. Terahertz dielectric waveguides exhibit the merits of small measurement volume, long interaction length, high signal-to-noise ratio (SNR), and so on.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Terahertz (THz) waves are extensively used in chemical and biological sensing, [1][2][3] medical [4][5][6] and near-field imaging, [7,8] onchip communication, [9,10] foodstuffs, drug inspections, [11][12][13] and spectroscopy. [14][15][16] Constructing on-chip integrated THz devices carrying energy profiles in subwavelength scale is of great potential for various applications. In visible and near-infrared regimes, exciting surface plasmon polaritons (SPPs), [17][18][19][20] the collective oscillations of electrons at a dielectric metal interface, using Previous studies, such as, the references [47][48][49][50][51][52][53][54][55] have reported the guiding mechanism of IGP.…”
Section: Introductionmentioning
confidence: 99%